Emerging and Developing Economies : Ten Years After the Global Recession - Kose, M. Ayhan; Ohnsorge, Franziska (World Bank, Washington, DC, 2020)
Although emerging market and developing economies (EMDEs) weathered the global recession a decade ago relatively well, they now appear less well placed to cope with the substantial downside risks facing the global economy. In many EMDEs, the room for monetary and fiscal policies to respond to shocks has eroded; underlying growth potential has slowed; and the momentum for improving policy frameworks, institutions, and business climates seems to have slackened. The experience of the 2009 global recession highlights once again the critical role of policy room in shielding economic activity during adverse shocks. The subsequent decade of anemic growth underlines the need for sound policy frameworks, institutions, and business environments to promote sustained growth. With the global growth outlook weakening and vulnerabilities rising, the policy priority for EMDEs is now to improve resilience to shocks and to lift long-term growth prospects.